(untitled) (Olhares, 2025)
This article introduces the concept of a walkshop, an artistic and pedagogical practice based on walking and engaging in encounters with the cityscape. Performers and participants partake in an experience that mediates other forms of relationship with the city while they circulate, contemplate, and discover its spaces, acknowledging its inhabitants and their singularities. When we focus attention on the path and the act of walking, the focus of this movement shifts away from the point that we are directed towards and becomes the journey itself. Moving in a nonfunctional manner transforms walking into an artistic, aesthetic, and political action. As our case in point for this reflection, we concentrate on Walkshop Paris which took place in the French capital on 24 June 2022 during the “Theatre and the City” conference.